Implementasi Kebijakan Pengembangan Kurikulum di Madrasah Aliyah Negeri 2 Model Medan - Maulidayani Maulidayani; Candra Wijaya; Asnil Aida Ritonga (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to analyze the implementation of curriculum development policies at MAN 2 Model Medan, 1) What are the steps for implementing curriculum development policies at Madrasah Aliyah Negeri 2 Medan Model?, 2) What is the process of implementing curriculum development policies at Madrasah Aliyah Negeri 2 Medan Model? ?, 3) How is the monitoring and evaluation of the implementation of curriculum development policies at Madrasah Aliyah Negeri 2 Model Medan? Data collection techniques using interview techniques, observation and document studies. Analysis of the research data uses the steps proposed by Miles & Hubermun (1994) which include data reduction, data presentation and conclusions. In strengthening the validity of the data findings and the authenticity of the research, the researcher refers to the use of data validity standards suggested by Lincoln & Guba (1985), which consist of credibility, transferability, dependability and confirmability. The results of this study found: 1) The steps for implementing curriculum development policies at Madrasah Aliyah Negeri 2 Model Medan are top down. This curriculum development policy makes madrasas apply two types of curriculum, namely the 2013 Curriculum and SKS. The implementation of this curriculum development policy also involves teachers, staff, WKM, and Madrasah Committees. 2) The characteristics of the process of implementing curriculum development policies in the Medan Model 2 Madrasah Aliyah refer to the curriculum blueprint program. This document contains guidelines and matters related to the implementation of the curriculum at MAN 2 Model Medan. Overall, the process of implementing curriculum development policies at MAN 2 Model Medan is quite good, but still needs to overcome existing obstacles, namely related to the implementation of local content; and 3) Monitoring and evaluation of the implementation of curriculum development policies at Madrasah Aliyah Negeri 2 Model Medan was carried out 3 times, namely at the planning, implementation, and final stages of the program. This is done to maintain the quality of the madrasah and meet the established quality standards.